Acetylcholinesterase Inhibitory Meroterpenoid from a Mangrove Endophytic Fungus Aspergillus sp. 16-5c - Long, Yuhua (Molecules, 2017)
One new meroterpenoid, named 2-hydroacetoxydehydroaustin (1), together with nine known meroterpenoids, 11-acetoxyisoaustinone (2), isoaustinol (3), austin (4), austinol (5), acetoxydehydroaustin (6), dehydroaustin (7), dehydroaustinol (8), preaustinoid A2 (9), and 1,2-dihydro-acetoxydehydroaustin B (10), were isolated from the mangrove endophytic fungus, Aspergillus sp. 16-5c. These structures were characterized by spectroscopic analysis, further the absolute configurations of stereogenic carbons for Compounds 1, 3, 4, 6, 7, 8, 9, and 10 were determined by single crystal X-ray diffraction analysis using Cu Kα radiation. Moreover, the absolute configurations of stereogenic carbons for Known Compounds 3, 7, 8, and 9 are identified here for the first time. Compounds 3, 7, and 8 showed acetylcholinesterase (AchE) inhibitory activity with IC(50) values of 2.50, 0.40, and 3.00 μM, respectively.